Analysis of the privatization process in Poland in the years 2008-2011: Outcomes and prospects - Wiktor Patena (e-Finanse: Financial Internet Quarterly, 2014)
The paper focuses on the analysis of the privatization process conducted in the years 2008-2011 with an attempt to show a broad picture of privatization in Poland, indicate resources that still exist although hidden and show government practices in making privatization more effective or, on the contrary, in carrying out quasi-privatization practices. Three main issues are discussed. First, the privatization process that took place in 2008 - 2011 seems to be to some extent only sham privatization - many of the companies were simply communalized, or transferred to other state-controlled companies and various government agencies. Thus, contrary to opinions expressed by the government officials, the privatization process is far from being terminated. A new approach used by the Ministry of Treasury is to create special purpose vehicles in order to sell the state-controlled assets more effectively. It turns out that 76% of privatized enterprises in the years 2008 - 2011 were sold via a tender or auction mechanism - the rest can be considered sham privatization. Huge resources are still to be privatized - the companies have to be identified and should report to one government agency. The novelty is the government's approach to privatization which involves packing assets into one market attractive entity. The hypothesis verification is preceded with analysis of privatization in Poland in the years 1989 - 2007, its relations with politics and the economic situation.
Keywords: G38; H27; L33; 330; privatization revenues; company performance; state-owned enterprises